Pre-Service Teachers’ Perception About the Use of ICT in Teaching and Learning Context - Iroh Magfiroh (National Conference on Language, Education, and Technology Proceeding, 2021)
Currently, information and communication technology (ICT) are becoming indispensable tool for learning, particularly computer multimedia and internet resources. One of the ICT learning models is e-learning. This paper investigates perception of the use of ICT by pre-service teachers from Indonesia who teach at one junior high school in Philippines. There were 2 teachers who participated in the study, they were required to complete the answer several open-ended questions. There were some problems revealed which were related to skills, knowledge and managing issues such as training, preparation and its effective use. Keywords: Information and communication technology (ICT); e-learning